Pantai Sepat in Kuantan, Pahang: a picture-perfect scenery / Farhan Faat … [et al.] - Faat, Farhan; Salim, Shahrool Rezza; Salleh, Rashid; Mohd Fisol, Nadia Maisarah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
At the stroke of midnight in Kuantan, Pahang, we stepped into the tranquil public beach Pantai Sepat. As it awaited for our arrival, the beach lay in a serene darkness, exposing its undulating curves and the soft murmuring of the South China Sea. Our vehicle's headlights briefly illuminated the peaceful expanse before we turned them off, allowing them to merge into the lunar terrain and pierce through the night like twin beacons. We carefully emptied our camping gear onto the soft grass. With the moon's silvery light reflecting off the lake and the sky seeming like an inkblot of stars, the scene was like something out of a fairy tale. Very quickly, our tents were set up, and the fabric began to rustle in the slightest breeze. As the darkness fell, our eyes grew tired. We crawled into our mattress and sought refuge where the soothing sound of the waves played like a soothing song. Our airtight tents protected us from the night's cold, and the soothing sound of the waves rocked us to a restorative slumber.